نحو رقمنة المؤسسات الإعلامية في ظل الألفية الثالثة : واقع وآفاق - جابري سارة; بوطورة اكرم (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
كنتيجة حتمية للتطورات التقنية والتكنولوجية التي يعرفها عصرنا الحالي. والذي أصبح يسمى بالعصر الرقمي نتاجا للاستخدام المكثف للتكنولوجيات الرقمية في جميع مجالات الحياة والمعرفة ولعل أبرز هذه التقنيات أو التحولات ما يعرف اليوم بالرقمنة التي غيرت جذريا طرق التعامل مع المعلومات في جميع القطاعات بصفة عامة وقطاع المكتبات والمعلومات بصفة خاصة. والتي أصبحت بمثابة جسر للتحول نحو العالم الرقمي والإلكتروني أو إحدى الأدوات الأساسية لإرساء قواعد مجتمع المعلومات، لقد أدركت مؤسسات المعلومات والمؤسسات الاعلامية الجزائرية الأهمية التي تكتسيها الرقمنة في تطوير وعصرنة المؤسسات، وهذا ما يتجلى من خلال انطلاق بعض من المؤسسات بمختلف أنواعها في تجسيد مشاريع رقمية وفي إدخال التقنية الحديثة وإنشاء المكتبات الرقمية فضلا عن التوجه نحو الاعلام الرقمي سعيا منها للارتقاء بخدماتها بما يتناسب ويتجاوب مع متطلبات مستفيديها. As an inevitable result of technical and technological developments known in our time. Which has become called the digital age as a result of the extensive use of digital technologies in all areas of life and knowledge, and perhaps the most prominent of these technologies or transformations, The transformations are what is known today as digitization, which has radically changed the ways of dealing with information in all sectors in general and the library and information sector in particular. Which has become a bridge to the transformation towards the digital and electronic world or one of the basic tools for establishing the rules of the information society, Algerian information and media institutions have realized the importance of digitization in the development and modernization of institutions, This is reflected in the launch of some institutions of various kinds in the embodiment of digital projects, the introduction of modern technology and the establishment of digital libraries, as well as the trend towards digital media in an effort to upgrade their services in a manner that is commensurate with and responds to the requirements of their beneficiaries.